Abuse of Rights by Majority Shareholders in Indonesian Family-Owned Company: Is It Likely? - Fiona Priscilia Kohar; Yetty Komalasari Dewi (Sriwijaya Law Review, 2021)
The familial relations entwining the ownership and management of a family-owned company creates a significant opportunity for majority shareholders to exercise their rights to others' detriment. Various jurisdictions have addressed such issue by projecting the concept of abuse of rights by majority shareholders (abus de majoritÃ©). The concept aims to detect which behaviour could be considered an abuse and provide legal protection for minority shareholders and companies. In Indonesia, however, such a concept has not been explicitly adopted nor discussed at length.  This work examines what behaviour which could be considered as a form of abuse of rights by majority shareholders under the Indonesian company law, and how the protection and practice of Indonesian private company law against such behaviour. This work is a normative legal research using conceptual, comparison, statutory, and case-law approaches. The comparison and case-law approaches will be utilized to examine the universal concept of majority shareholders abuse of rights by examining the adoption of the concept in various jurisdictions and examine several relevant cases brought to the Indonesian court. As a result, it concludes that there are still problems surrounding the legal measures available, as this behaviour is still prevalent, especially in Indonesia's family-owned companies. Hence, more stringent rules are needed to protect minority shareholders and the Indonesian Company's interests effectively.